Chapter The Multiple Roles of Tyrosinase-Related Protein-2/L- Dopachrome Tautomerase in Melanoma: Biomarker, Therapeutic Target, and Molecular Driver in Tumor Progression - Negroiu, Gabriela (InTechOpen, 2018)
Cutaneous malignant melanoma (CMM), which is ranked as the 8th most common cancers in the US, makes 4-7% of skin cancers but it causes approximately 80% of skin cancer deaths. CMM is characterized by insidious and fast progression, heterogenic evolution, and significant resistance to numerous therapeutic strategies. CMM is the result of the uncontrolled proliferation of melanocytes, the cells which reside in the basal layer of the epidermis. The most efficient therapy is the surgical removal if the lesion is in an early stage. For metastatic melanomas, there are different strategies, extremely rarely leading to total cure. Tyrosinase-related protein-2 (TRP2) or L-Dopachrome tautomerase (L-DCT) is a member of Tyrosinase-related protein family known for many years for its enzymatic activity in the distal steps of melanogenesis. The modern DCT image is focusing more on processes and mechanisms related to cell development and response to environmental and therapeutic stressors in normal and transformed cell phenotypes. This chapter provides an extended, updated biological status of TRP2/L-DCT encompassing the structural and functional particularities within melanoma molecularity, in the attempt to get new insights into the complex mechanisms of this neoplasm and raise the interest for DCT unexplored yet potential in melanoma diagnosis/prognosis and therapy.